Phased Array Antennas and their Localisation Capability - Enugu , Abonyi D.O; K. J, Offor (African Journal of Education,Science and Technology (AJEST), 2016)
Localisation is an unavoidable practise in the world because naturally man keeps searching for one thing or the other in his daily life. With the growth in technology, these naturally occurring search is advancing rapidly to accommodate more search objects like aircrafts, mobile phones, moving vehicles, tags in shops etc. Localization is therefore the process of trying to electronically locate the position of objects in space. These electronic search has been implemented in different ways like in Radio Frequency Identification (RFID), RADAR, GPS, Remote sensing and also in our popular cellular mobile communication where BTS must locate the MS for communication to occur. This paper x-rays the theory of phased array antennas and with simulation of uniform linear antenna array radiation patterns, showed how localisation can be achieved using RSS algorithm. Pre-determined patterns were obtained by simulation of 2-element antennas in space. The two antenna array system was located at the centre of an x-y-plane and ten randomly scattered points were displayed randomly within the plane to represent the radio units which are at this point of this research stationary. Applying the theory which says that a directional antenna will have its maximum transmission or reception in the direction of its maximum gain, it was shown that the pattern with highest received signal strength for a particular node will have that node located at its region.